2000
DOI: 10.1097/00007632-200003150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Rate and Hydration on the Mechanical Properties of the Disc

Abstract: Intervertebral disc compressive mechanical properties are significantly dependent on loading rate and hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 20 publications
11
134
0
Order By: Relevance
“…Exposure to whole body high frequency loading/vibration was found to be associated with low back pain and disc degeneration [10,92]. Loading rate influences the extent of disc deformation, possibly also the rate of fluid flow in and out of the disc [88,95], and affects the biosynthesis of the IVD cell. A lower loading frequency of 0.5 Hz was found to be the best of the tested conditions (0.5, 1.5 and 2.5 Hz) in preserving proteoglycan content of the rat tail model [19].…”
Section: Response To Frequency Modulationmentioning
confidence: 99%
“…Exposure to whole body high frequency loading/vibration was found to be associated with low back pain and disc degeneration [10,92]. Loading rate influences the extent of disc deformation, possibly also the rate of fluid flow in and out of the disc [88,95], and affects the biosynthesis of the IVD cell. A lower loading frequency of 0.5 Hz was found to be the best of the tested conditions (0.5, 1.5 and 2.5 Hz) in preserving proteoglycan content of the rat tail model [19].…”
Section: Response To Frequency Modulationmentioning
confidence: 99%
“…For dynamic axial stiffness the values obtained are in the same range as the static ones. The static experiments showed that the values of this parameter are highly dependent on the displacement imposed on the specimen and are also dependent on the time [21]. The results must be analysed in the light of these findings.…”
Section: Resonant Frequencymentioning
confidence: 99%
“…The main one is that fluid flow causes variations in volume [2, 7,21] and in the mechanical properties of the disc [23]. Maintaining hydration during the experiments is therefore important [1,3,16,24].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Lumbar intervertebral discs change morphologically, biochemically, and biomechanically with advancing age, [1][2][3][4][5][6][7][8][9][10] changes that are characterized as disc degeneration and are implicated as the origin of low back pain. Unfortunately, the initiating and perpetuating factors of disc degeneration are unknown, so despite the pain, disability, and economic loss associated with disc degeneration, intervention and mitigation strategies cannot effectively proceed.…”
mentioning
confidence: 99%